Bycatch of Loggerhead Turtle (Caretta caretta) in the Italian Adriatic Midwater Pair Trawl Fishery - Pulcinella, Jacopo; Bonanomi, Sara; Colombelli, Alessandro; Fortuna, Caterina Maria; Moro, Fabrizio; Lucchetti, Alessandro; Sala, Antonello (Frontiers in Marine Science, 2019)
Despite the fact that Mediterranean loggerhead turtles are listed as ‘Least Concern’ by the IUCN, they are among the most threatened long-lived marine species worldwide, because of fishery-related incidental captures. The northern central Adriatic Sea is one of the most overfished basins of the Mediterranean Sea and it supports a very valuable marine biodiversity, including sea turtles. This study assesses the spatial and seasonal impact of the northern central Adriatic pelagic/mid-water pair trawl fishery on loggerhead turtle (Caretta caretta) by examining incidental catches recorded between 2006 and 2018 and environmental variables. The model predicted seasonal variation of loggerhead distribution. According to previous studies, data analysis indicates that most bycatch events of loggerhead turtle occurred in the northern Adriatic Sea. The present data confirm that the northern Adriatic may be an important foraging area for loggerhead turtle. They also highlight the urgent need for a better understanding of the interactions between sea turtles and fisheries to develop and apply suitable, ad hoc management measures in critical habitats.